Clockwork Angel: The Infernal Devices #1 - Clare, Cassandra (New York : Margaret K. McElderry Books, 2010)
When sixteen-year-old orphan Tessa Fell's older brother suddenly vanishes, her search for him leads her into Victorian-era London's dangerous supernatural underworld, and when she discovers that she herself is a Downworlder, she must learn to trust the demon-killing Shadowhunters if she ever wants to learn to control her powers and find her brother.
Tessa Fell's search for her missing brother leads her into Victorian London's supernatural underworld, where she must learn to trust the demon-killing Shadowhunters if she wants to learn to control her powers and find her brother.
Ages 14 up.
Keywords: Supernatural -- Fiction; Demonology -- Fiction; Orphans -- Fiction; Secret societies -- Fiction; London (England) -- History -- 19th century -- Fiction; Supernatural -- fiction; Demonology -- Fiction; Orphans -- Fiction; Secret societies -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; London (England) -- History -- 19th century -- Fiction; Great Britain -- History -- 19th century -- Fiction